Measuring resilience for Chinese-speaking populations: a systematic review of Chinese resilience scales - Tian, Zhenyu; Kuang, Kai; Wilson, Steven R.; Buzzanell, Patrice M.; Ye, Jinyi; Mao, Xinyue; Wei, Hai (Frontiers in Psychology, 2024)
Despite the rapid growth of interdisciplinary resilience research in Chinese contexts, no study has systematically reviewed available individual-level measurement scales for Chinese-speaking populations. We report a systematic review of scales developed for or translated/adapted to Chinesespeaking contexts. Analyses of 963 qualified studies published between 2015-2020 suggest that Chinese resilience scales have been used in a diverse range of study contexts. Among 88 unique kinds of individual resilience measures, we highlight and evaluate the three most frequently used translated scales and a matching number of locally developed scales (nine scales in total considering variations such as short forms) by seven methodological criteria. Based on the review results, we discuss how future research may advance scale development and translation work in Chinese contexts, such as by following specific procedures for ensuring rigor in translating scales developed in different source languages. We also address issues and challenges in measuring resilience as a process and call on researchers to further develop/evaluate process measures for Chinese-speaking populations.